“Ya Ne Zabudu Svoyei Kolybelnoi…” by Pyotr Vegin: a Genre-Oriented Analysis - Ivaniuk, Boris (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2021)
Pyotr Vegin’s text “Ya ne zabudu svoyei kolybelnoi…” [‘I won’t forget my lullaby’] is weaved of multi-genre motives. Its analysis in the paper substantiates the conclusion that the writer continues the genre history of “the last poem”, valediction and visionary poetry, and that he adopts a polemical stance toward the Horatian tradition of “poetic monuments”. In classical texts, starting with Horace’s “Exegi monumentum...”, which are rhetorical and open to public discussion and part of a poetic agon, the poet’s posthumous fame is compared with artifacts of material memory that are being belittled for the sake of the author’s self-aggrandisement. Vegin’s “monument” is, by contrast, dendronic (a ‘Lombardy poplar’) and his poetic voice soft, addressless, and not expecting response. In juxtaposing Vegin’s text with Pushkin’s “Ya pamyatnik sebe vozdvig nerukotvornyi” (‘I’ve raised myself a monument not built by human hands’), what is evident is a lowering down of the romantic image of the lyre (Pushkin’s ‘my soul in the sacred lyre’) as the sign of the creative legacy bequeathed to the scions, or, in a broader sense, as an allegory of the poetic tradition. As distinguished from the mainly ironic revaluation of this tradition by Vegin’s contemporaries, his polemic with it is undertaken, as it were, from inside, by means of a metaphoric resemantisation of its stylistic formulas, while at the same time leads to creating Vegin’s individual version of a “poetic monument”. His is semantically oriented not on the immortality of the author’s artistic legacy but on an individual reincarnation, a resurrection that excludes death as such by dint of the poet’s carnal death, which has served as the event around which the poetic text is build.